The purpose of playing : Shakespeare and the cultural politics of the Elizabethan theatre - Montrose, Louis (Chicago and London : The University of Chicago Press, 1996)
Part of a larger project to examine the Elizabethan politics of representation, Louis Montrose's The Purpose of Playing refigures the social and cultural context within which Elizabethan drama was created.

Montrose first locates the public and professional theater within the ideological and material framework of Elizabethan culture. He considers the role of the professional theater and theatricality in the cultural transformation that was concurrent with religious and socio-political change, and then concentrates upon the formal means by which Shakespeare's Elizabethan plays called into question the absolutist assertions of the Elizabethan state. Drawing dramatic examples from the genres of tragedy and history, Montrose finally focuses his cultural-historical perspective on A Midsummer Night's Dream.

The Purpose of Playing elegantly demonstrates how language and literary imagination shape cultural value, belief, and understanding; social distinction and interaction; and political control and contestation.
Bibliografija uz tekst
Kazalo
Keywords: Shakespeare, William; kazalište; moć